Graduate band conducting recital: lesson plans and theoretical/historical analysis of literature - Sweaney, Roselyn Dawn (Kansas State University, 2009)
This report contains lesson plans, historical information and a theoretical analysis of the literature performed in the Spring Concert of the Sedan Jr./Sr. High Concert Band under the direction of Roselyn Sweaney. The recital was held on Tuesday, April 28, 2009 in the “New Gym” of the Sedan Jr./Sr. High School. The recital featured performances by the following ensembles: 5th Grade String Ensemble, 5th Grade Band, 6th Grade Band, 5th & 6th Grade Bands joined for 2 selections, Jr./Sr. High Concert Band. The 5th Grade String Ensemble played Lightly Row, This Old Man, French Folk Song, Bingo and The William Tell Overture. The 5th Grade Band played Downtown Blues, Sounds of Beale Street, Barbara Ann and Hard Rock Blues and the 6th Grade Band played Brave New World, Sir Lancelot, Percussion On Parade and Surprise Symphony. The 5th & 6th Grade Bands joined together to play Soul Swinger. The Jr./Sr. High Concert Band performed Crestwood by Nancy Seward, Shaker Variants by Elliot Del Borgo, Rock ‘N’ Roll Explosion! arranged by Jerry Nowak, America, The Beautiful arranged by Dale Casteel, Miss Liberty March by Karl King, arranged by James Swearingen. Lauren Miller also performed a trumpet solo, Aria by George Golterman. Lauren had received a “I” for her trumpet solo at State Music Festival. The concert was directed by Mrs. Rosie Sweaney and by ½ time teacher, Miss Trish Roudybush. This was Miss Roudybush’s first year of teaching, following her student teaching and implementation of the string program at Sedan during the 2007-08 school year.
Keywords: Score; Analysis; Education, Music (0522); Music (0413)